2017
DOI: 10.1097/anc.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability as a Feeding Intervention Outcome Measure in the Preterm Infant

Abstract: Background Feeding interventions for preterm infants aim to reduce the physiologic stress of feeding to promote growth. Heart rate variability (HRV) is a potential non-invasive measure of physiologic stress that may be useful for evaluating efficacy of feeding interventions. Purpose To evaluate whether HRV is a sensitive measure of physiologic stress compared to standard physiologic outcomes in the context of a feeding intervention study. Methods This was secondary analysis of a within-subjects, cross-over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
3
2
Order By: Relevance
“…Table 3 displays HRV indices between ECG and RRi files, which are consistent with other reports of infant HRV in the first month of life (Bartels et al, 2017;Longin et al, 2005;Pados et al, 2017;Patural et al, 2008). However, the current study shows the RMSSD measure to be more sensitive to variations in methodology, namely file type.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Table 3 displays HRV indices between ECG and RRi files, which are consistent with other reports of infant HRV in the first month of life (Bartels et al, 2017;Longin et al, 2005;Pados et al, 2017;Patural et al, 2008). However, the current study shows the RMSSD measure to be more sensitive to variations in methodology, namely file type.…”
Section: Discussionsupporting
confidence: 89%
“…The LF ranges in these studies differ by 0.05 Hz, and the studies use a similar upper limit of 1.5 Hz for HF. Most groups extend the HF band to 1.33 Hz (Pados et al, 2017) or 1.5 Hz (Bartels et al, 2017; Javorka et al, 2017; Kozar et al, 2018) to account for increased infant respiratory rate. The HF upper limit is over three times larger than the HF upper limit seen for adults.…”
Section: Discussionmentioning
confidence: 99%
“…In congruence with these findings, Pados et al using a co-regulatory feeding support approach that focused on reduction of environmental stimuli in the NICU, also found that the number of apnea events decreased during feeding, and the approach supported infants to breathe better during feedings. Unlike this current study, however, oxygen desaturation events failed to differ between the control and intervention groups [27]. On average, preterm infants in the behavioral-cue-based feeding group in this study acquired oral feeding skills 3 days earlier than the control group, and although this difference was not statistically significant, it had clinical and economic significance.…”
Section: Discussioncontrasting
confidence: 81%
“…In congruence with these ndings, Britt et al using a coregulatory feeding support approach that focused on reduction of environmental stimuli in the NICU, also found that the number of apnea events decreased during feeding, and the approach supported infants to breathe better during feedings. Unlike this current study, however, oxygen desaturation events failed to differ between the control and intervention groups [32].On average, preterm infants in the behavioral-cuebased feeding group in this study acquired oral feeding skills three days earlier than the control group, and although this difference was not statistically signi cant, it had clinical and economic signi cance.…”
Section: Discussioncontrasting
confidence: 76%